Self efficacy for fruit, vegetable and water intakes: Expanded and abbreviated scales from item response modeling analyses - Cullen Karen W; Baranowski Janice C; Bachman Christine; Watson Kathleen B; Baranowski Tom; Thompson Debbe; Siega Riz Anna-Maria (BMC, 2010)
Abstract Objective To improve an existing measure of fruit and vegetable intake self efficacy by including items that varied on levels of difficulty, and testing a corresponding measure of water intake self efficacy. Design Cross sectional assessment. Items were modified to have easy, moderate and difficult levels of self efficacy. Classical test theory and item response modeling were applied. Setting One middle school at each of seven participating sites (Houston TX, Irvine CA, Philadelphia PA, Pittsburg PA, Portland OR, rural NC, and San Antonio TX). Subjects 714 6th grade students. Results Adding items to reflect level (low, medium, high) of self efficacy for fruit and vegetable intake achieved scale reliability and validity comparable to existing scales, but the distribution of items across the latent variable did not improve. Selecting items from among clusters of items at similar levels of difficulty along the latent variable resulted in an abbreviated scale with psychometric characteristics comparable to the full scale, except for reliability. Conclusions The abbreviated scale can reduce participant burden. Additional research is necessary to generate items that better distribute across the latent variable. Additional items may need to tap confidence in overcoming more diverse barriers to dietary intake.